THE PROBLEM OF STUDYING AND IMPLEMENTING THE ORIGIN CATEGORY IN THE UZBEK LANGUAGE (TAMADDUN NURI JURNALI, 2024)
In this article, the study of the category of agreement in the Uzbek language and its implementation were clearly described. Category of agreement in uzbek language and how they are used have been discussed. Also, interactive methods were used and analyzed.